Didi [videorecording (Blu-Ray)] - Wang, Sean, (Director); Davis, Sam A.; Zakowski, Arielle; Greco, Giosuè; Wang, Izaac; Chen, Shirley; Chang, Li Hua (Actor); Chen, Joan, 1961- (Universal Pictures Home Entertainment, 2024)
In 2008, during the last month of summer before high school begins, an impressionable 13-year-old Taiwanese-American boy learns what his family can't teach him: how to skate, how to flirt, and how to love your mom.